2008
DOI: 10.1097/gim.0b013e318164e4f5
|View full text |Cite
|
Sign up to set email alerts
|

Great expectations: views of genetic research participants regarding current and future genetic studies

Abstract: Purpose: Recruitment of prior participants in genetic research is one strategy suggested to maximize efficient use of research dollars in gene-environment studies. We explored attitudes toward genetic research participation among people in a case-control genetic epidemiology study of colon cancer, the North Carolina Colorectal Cancer Study (NCCCS). Methods: Quantitative and qualitative cross-sectional analysis of 801 NCCCS participants.Results: Participants were "very positive" (63%) or "positive" (32%) about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
43
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 15 publications
(11 reference statements)
13
43
4
Order By: Relevance
“…Participants identified trust in the research organization as a key positive influence to participation in genetic research. This finding is consistent with other studies [18,24,25,26], and trust in the research organization has been identified as particularly important in recruiting minority research participants [25]. Considerable discussion occurred in both group types concerning lack of trust in governmental oversight of genetic research data and the need for transparency in data sharing and monitoring policies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Participants identified trust in the research organization as a key positive influence to participation in genetic research. This finding is consistent with other studies [18,24,25,26], and trust in the research organization has been identified as particularly important in recruiting minority research participants [25]. Considerable discussion occurred in both group types concerning lack of trust in governmental oversight of genetic research data and the need for transparency in data sharing and monitoring policies.…”
Section: Discussionsupporting
confidence: 81%
“…Other investigators have similarly found that education, particularly about the complex information involved in data sharing and genetic research, should be broadly communicated and aimed at the public and targeted research populations [18,26]. Focus group participants offered education methods and strategies they thought would be most suitable for the public.…”
Section: Discussionmentioning
confidence: 99%
“…Those not working in the health care field were particularly susceptible to these misunderstandings. Such high public expectations of genetics have been observed in other studies [31,32,33]. The misperceptions observed in this relatively highly educated study population, particularly conflating testing for common complex diseases with that for single-gene disorders and reproductive genetics, suggests that members of the public will not easily distinguish between the ‘old’ paradigm of genetic disorders and the ‘new’ paradigm of genomic risk information for chronic complex diseases [34].…”
Section: Discussionmentioning
confidence: 89%
“…In disease-specific biobank research settings, it is the identification with the disease being studied (through personal or familial experience), which appeared to play a decisive role among donors [13][14][15]. The idea of belonging to a group of people suffering the same condition acts as a triggering factor as well as the wish to invest in the future health of an 'imagined community' [16].…”
mentioning
confidence: 99%